Keys to confidence and competence in English 1 : reading, study skills and grammar workbook - Yu, Pamela; Miranda-Plata, Sterling (Laguna, Philippines : Trailblazer Publications, 2012)
This book will serve as your mentor. It starts by training you to access your strengths/weaknesses, to set your own goals, and to monitor your progress. This workbook will also develop your critical thinking and problem-solving skills as the information age demands higher order thinking.
Lesson 1. Critical thinking -- Lesson 2. Critical learning -- Lesson 3. Reading purposes -- Lesson 4. Reading strategies, organizers, and tools -- Lesson 5. Reading details -- Lesson 6. Reading vocabulary -- Lesson 7. Reading patterns -- Lesson 8. Reading inferences -- Lesson 9. Reading non-prose forms -- Lesson 10. Reading and evaluation.
Keywords: COMMUNICATION -- GRAMMAR -- READING -- WORBOOK